2021
DOI: 10.3389/fonc.2021.769592
|View full text |Cite
|
Sign up to set email alerts
|

ITGA5 Predicts Dual-Drug Resistance to Temozolomide and Bevacizumab in Glioma

Abstract: AimsAnti-angiotherapy (Bevacizumab) is currently regarded as a promising option for glioma patients who are resistant to temozolomide (TMZ) treatment. But ongoing clinical research failed to meet therapeutic expectations. This study aimed to explore the pivotal genetic feature responsible for TMZ and Bevacizumab resistance in glioma patients.MethodsWe downloaded the transcriptomic and methylation data of glioma patients from The Cancer Genome Atlas (TCGA), Chinese Glioma Genome Atlas (CGGA), and Gene Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Recent proteomic analysis has revealed that small interfering RNA knockdown of ITGA5 reduces invadopodia formation in U87MG cells [ 48 ]. Moreover, both the epigenetic and transcriptional levels of ITGA5 are effective in predicting TMZ and bevacizumab resistance, revealing the novel roles of ITGA5 in predicting the treatment outcomes of glioma [ 49 ]. To eliminate the malignance of GBM with highly expressed integrin-α5β3, various anti-integrin agents, such as RGD-containing peptides, have been developed; RGD peptides can be used as selective carriers to deliver anti-cancer drugs, and have shown strong anti-glioma efficacy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent proteomic analysis has revealed that small interfering RNA knockdown of ITGA5 reduces invadopodia formation in U87MG cells [ 48 ]. Moreover, both the epigenetic and transcriptional levels of ITGA5 are effective in predicting TMZ and bevacizumab resistance, revealing the novel roles of ITGA5 in predicting the treatment outcomes of glioma [ 49 ]. To eliminate the malignance of GBM with highly expressed integrin-α5β3, various anti-integrin agents, such as RGD-containing peptides, have been developed; RGD peptides can be used as selective carriers to deliver anti-cancer drugs, and have shown strong anti-glioma efficacy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TMZ‐resistant U87MG cell line (U87MG‐TMZ‐R) was constructed as mentioned in our previous research. 14 Total RNA of U87MG and U87MG‐TMZ‐R cells were extracted with Trizol reagent, for isolating poly(A)‐containing mRNA and noncoding RNA with beads bearing oligo(dT). Sequenced reads were trimmed for adaptor sequence and masked for low‐complexity or low‐quality sequences, then mapped to the hg19 whole genome using HISAT2.…”
Section: Methodsmentioning
confidence: 99%
“…The TMZ‐resistant U87MG cell line (U87MG‐TMZ‐R) was constructed as mentioned in our previous research 14 . Total RNA of U87MG and U87MG‐TMZ‐R cells were extracted with Trizol reagent, for isolating poly(A)‐containing mRNA and noncoding RNA with beads bearing oligo(dT).…”
Section: Methodsmentioning
confidence: 99%
“…For example, astrocytes have been shown to increase GBM survival and resistance against TMZ in coculture condition as compared to monoculture condition 11–14 . ECs are an important component of the perivascular niche and are responsible for increased resistance of GBM cells against TMZ 15–17 . GBM stem cell‐like cells are a subpopulation of GBM cells that express stemness‐related markers like NESTIN, SOX2, CD133, NANOG, and OCT4, have been reported to have high self‐renewal, multilineage differentiation, and heightened resistance to therapeutic treatments 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] ECs are an important component of the perivascular niche and are responsible for increased resistance of GBM cells against TMZ. [15][16][17] GBM stem cell-like cells are a subpopulation of GBM cells that express stemness-related markers like NESTIN, SOX2, CD133, NANOG, and OCT4, have been reported to have high self-renewal, multilineage differentiation, and heightened resistance to therapeutic treatments. 8,9 These cells can also trans-differentiate into ECs and enhance the resistance to antiangiogenic therapy, thereby resulting in treatment failure in GBM.…”
mentioning
confidence: 99%